MODELING AND EVALUATION OF PROJECT RISKS IN MULTI-PROJECT ENVIRONMENT - Lytvyn, Vasyl; Rishnyak, Ihor (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The article describes risk model of the project that operates in the multi-project environment. A formal assessment of project risks was presented. Approaches to risk assessment on various criteria are given.